Kirk-Othmer Encyclopedia of Chemical Technology 2002
DOI: 10.1002/0471238961.16081520230920.a01
|View full text |Cite
|
Sign up to set email alerts
|

Photothermographic and Thermographic Imaging Materials

Abstract: Photothermographic and thermographic imaging technology based on silver carboxylates have evolved into high quality black and white imaging materials suitable for extremely demanding applications such as medical X‐ray and graphic arts films. the unique ability of generating a high quality image that requires only dry processing, without any of the hazards and environmental problems of conventional, wet‐processed films for these applications, has provided significant new commercial opportunities for this techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…In order to obtain silver nanoparticles under mild conditions, thermally unstable intermediate which could react easily with the reducing agent was synthesized [19]. The reaction of silver stearate with triphenylphosphine has been investigated [23], and one kind of new silver complex containing triphenylphosphine was reported [24]. Compared with silver stearate, the new silver complex was more soluble and reactive.…”
Section: Resultsmentioning
confidence: 99%
“…In order to obtain silver nanoparticles under mild conditions, thermally unstable intermediate which could react easily with the reducing agent was synthesized [19]. The reaction of silver stearate with triphenylphosphine has been investigated [23], and one kind of new silver complex containing triphenylphosphine was reported [24]. Compared with silver stearate, the new silver complex was more soluble and reactive.…”
Section: Resultsmentioning
confidence: 99%
“…We have found that the same reaction occurs with long chain length silver carboxylates, such as those found in a typical photothermographic construction, [10][11][12] albeit to a more limited extent. The Ag 2 S appears in all cases, but the yield is substantially different with some apparent relationship to the chain length.…”
Section: Introductionmentioning
confidence: 89%
“…8,9 In addition, MBI has been found to be an important component in photothermographic imaging materials, which are light exposed but thermally developed without conventional wet processing. [10][11][12] We reported the solid state structure of the ͓AgBr• MBI• ͑acetone͒ 0.5 ͔ 4 complex that is formed in organic solvent from MBI and the light sensitive component of photographic and photothermographic films. 13 Under those conditions, despite the labile proton available on the MBI, the ligand acts as a neutral donor, unlike its adsorption to silver halide surfaces in aqueous conditions.…”
Section: Introductionmentioning
confidence: 99%